Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray Terhadap Kemampuan Komunikasi Matematis Peserta Didik Kelas VIII SMPN 2 Pariaman - SILVIA MIMANDA (Jurnal Edukasi dan Penelitian Matematika, 2019)
Mathematical communication skills is one of the learning objectives that are expected to be achieved optimally by students. However  in reality the mathematical communication skills of studentis still not optimal. This is foundeed in class VIII of SMPN  2Pariaman. One of the  factor is learning that has not been fully able to facilitate student in developing mathematical communication properly. One effort that can be done is by applying the Two Stay Two Stray (TSTS) cooperative learning model. The purpose of this study is to describe whether the mathematical communication skills of studentwho learn by using the TSTS model is more better than student who learn by conventional learning and describe the development of mathematical communication skills of student during the application of the TSTS model. The type of research  is quasy experiment and descriptive, with a Randomized Control-Group Only Design. This shows that the mathematical communication skills of student who learn by applying the TSTS learning model is more better than the mathematical communication skills of studentwho learn by applying the conventional  learning. Keywords – Cooperative Learning ,Mathematical Communication Skills, Two Stay Two Stray